Colpocytology - Campos Rey de Castro, Jorge (2015)
The usefulness of cytodiagnosis in medical practice, is no longer subject discussed; abundant literature accumulated in the fourth and fifth decades of this century has demonstrated the accuracy of the method and has also proved that the cytodiagnosis offers different possibilities, whichever is the territory of the organism in which it is applied or the type of discharge or exudate under review. All authors agree that the method achieves the best results when it is applied to the pelvic area.